Development of Biopreneurship Project-Based Module for Junior High School Students in Mandalika Lombok Special Economic Zone - M. Akhyar Rosyidi; A. Wahab Jufri; I Putu Artayasa (Jurnal Penelitian Pendidikan IPA, 2023)
The development of entrepreneurial literacy is crucial for students to prepare themselves to benefit from the current development of the Mandalika Lombok Special Economic Zone (SEZ). The purpose of this study is to develop a project-based science module focusing on biopreneurship to enhance students' entrepreneurial literacy. This research is a development study that adopts the Dick and Carey model. The research data consist of a description of the development of the science module and its theoretical feasibility. The feasibility of the science module is analyzed using Aiken’s V formula. The research results indicate that the expert assessment of the feasibility of the biopreneurship-based project-based science module shows a percentage of 77.3% in the category of being suitable for use. Meanwhile, the biopreneurship project worksheets have a percentage of 73.9% in the category of being suitable for use. Additionally, the learning steps have a percentage of 80.0% in the category of being suitable for use in teaching and learning. The conclusion of this study is that the development of the project-based biopreneurship science module can be effectivelyi used to enhance students' entrepreneurial literacy.